Oral proliferative verrucous leukoplakia: An enigmatic lesion with emphasis on its differential diagnosis - Pooja Madki; Ruheena Khan; M L Avinash Tejasvi; Shilpa Javudi (Wolters Kluwer Medknow Publications, 2020)
Oral proliferative verrucous leukoplakia (OPVL) is a distinct clinical form of oral leukoplakia (OL). It is one of the rare clinicopathological entities that is considered as a potentially malignant oral mucosal disorder with an increased rate of progression to oral squamous cell carcinoma (OSCC) and a very high recurrence rate. Initially, the condition develops as focal clinical hyperkeratosis that progresses gradually and becomes a wide multifocal disease with gross exophytic features. It is a slow-growing, long-term progressive, and enigmatic lesion that is difficult to define and disclose. We report here, a case of OPVL in the right mandibular alveolar ridge, clinical and diagnostic aspects, differential diagnosis, and histologic features of this relatively rare entity.